Efeitos do envelhecimento térmico e fotoquímico em ligantes asfálticos, mástique e matriz de agregados finos - Cravo, Margareth Carvalho Coutinho (2016)
The bituminous materials during its application and in service are exposed to a series of phenomena that enhance degradation. The laboratory tests simulating the short and long term aging, performed in oven and pressure vessel, submit the samples to aging at high temperatures and the presence of air, but does not include the influence of Ultraviolet radiation (UV) in the system and nor the participation of mineral aggregate. In this scenario, this work aims to study the chemical changes that occur during the different degradative processes, thermal and photochemical, using techniques such as Infrared, Liquid Chromatography, Heithaus Parameter, Nuclear Magnetic Ressonance and Molecular Weight Distribution in neat asphalt binderand orwith lignin (natural antioxidant). To studythe rheological behavior it was used the Christensen-Anderson model to calculate the R parameter and the linear amplitude sweeptest to know the damage tolerance of this material. Master curve and LAS were also carried out on fine aggregate matrix (FAM) and masticof hydrated limeand granite filler, to understand the behavior of these structures against different types of aging. The chemical and rheological analysis, in all tests showed different paths between the thermal and photochemical aging. In addition,lignin had a good response as an antioxidant for both degradative processes. Finally, the participation of fillers as an inhibitor or catalyst for oxidation reactions depend on the type of degradative process to which it is exposed.